Español - Español, Español; Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1987)
Proceeding in the same form as in part 1, in the present work we set up the study of the influence that the active coals mentioned in the former part exert upon the absorption of pyridoxine hidrochloride. The same as before, we observe different behaviour to both coals. Relating the results obtained with the given drugs, we find that the decrease of the bio-availability is more evident in the case of phenphormine chlorhydrate than that of piridoxine.